2008
DOI: 10.1111/j.1539-6924.2008.01083.x
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainties in Biologically‐Based Modeling of Formaldehyde‐Induced Respiratory Cancer Risk: Identification of Key Issues

Abstract: In a series of articles and a health-risk assessment report, scientists at the CIIT Hamner Institutes developed a model (CIIT model) for estimating respiratory cancer risk due to inhaled formaldehyde within a conceptual framework incorporating extensive mechanistic information and advanced computational methods at the toxicokinetic and toxicodynamic levels. Several regulatory bodies have utilized predictions from this model; on the other hand, upon detailed evaluation the California EPA has decided against doi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 57 publications
1
9
0
Order By: Relevance
“…As shown in Fig. 6 and discussed further in Subramaniam et al (2008, Fig. 3), these data show roughly an order of magnitude variation in the cell replication rate at a given flux.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…As shown in Fig. 6 and discussed further in Subramaniam et al (2008, Fig. 3), these data show roughly an order of magnitude variation in the cell replication rate at a given flux.…”
Section: Discussionsupporting
confidence: 58%
“…In the Conolly et al modeling, it is further assumed that the formaldehyde flux levels at which cell replication exceeds baseline rates remains essentially unchanged for initiated cells not only for the rodent but also when extrapolated to the human. These assumptions need to be viewed in the context of the uncertainty and variability in the data discussed further in Subramaniam et al (2008). In addition, it may be noted that there are some limited data indicating that exposure to formaldehyde can result in increased cell replication at doses far below those that are considered to be cytotoxic.…”
Section: Discussionmentioning
confidence: 99%
“…DPC are considered to be the main genotoxic lesions for FA and are used in human risk assessment modeling of FA exposures (Subramaniam et al, 2008). Thus, it is important to understand how human cells can cope with FA-induced DPC.…”
Section: Discussionmentioning
confidence: 99%
“…The most abundant DNA lesions formed by FA in cells are DNA-protein crosslinks (DPC), which have a much greater chemical stability than small DNA adducts (Quievryn and Zhitkovich, 2000). The dose-dependence of DPC formation and nasal cancers in FA-exposed animals showed a close correlation, leading to the use of DPC in modeling of cancer risks associated with human exposures (Subramaniam et al, 2008). Although it is frequently assumed that DPC are major contributors to FA toxicity, their role in specific toxic responses has not yet been assessed experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…Evaluation of biological and statistical uncertainties issues were determined to be necessary by Subramaniam et al (2008) Research was done on laypeople's view of results from a risk assessment study of hazards involved from cell phones and base stations. Siegrist et al (2008) showed how participants in the study were more confident with the outcome when the study indicated a risk and when their prior opinion was proved to be correct.…”
Section: Modeling and Probability Simulation Usingmentioning
confidence: 99%